Impact energy release mechanism and debris cloud forming behavior of LaCeAlCo active amorphous spherical fragment - Jinbei Zhao; Bingwen Zhou; Bin Ya; Linggang Meng; Pengcheng Ju; Xingguo Zhang (Journal of Materials Research and Technology)
To study the impact energy release behavior, damage effect behavior and space forming behavior of the debris cloud behind the target of La32.5Ce32.5Al10Co25 amorphous alloy spherical fragment, the impact energy release test of an amorphous fragment at different velocities is carried out by using a φ 14.5 mm ballistic gun launching device and a quasi-closed reaction vessel. The impact energy release damage behavior of fragments and the space-forming behavior of debris clouds are analyzed based on the fragment penetrating target fragmentation theory. The results show that the perforation mode of the amorphous fragment penetrating the 2A12 front target is mainly plug damage mode. The average oxygen content of amorphous fragments respectively is 27.73 % and 55.24 % at 793 m‧s−1 and 1397 m‧s−1. When the impact velocity is 1397 m‧s−1, the energy release efficiency of the amorphous fragment is the largest, which is about 65 % and the energy density is 4.7473 kJ‧g−1. When the critical activation reaction occurs, the critical impact velocity is 439 m‧s−1, and the critical impact pressure P0 is 9.02 GPa. The theoretical model of debris cloud space forming behind the target is established. The evolution law of debris cloud space and impact energy releases damage model of amorphous fragments is obtained.